A Giant Euthyroid Endemic Multinodular Goiter with No Obstructive or Compressive Symptoms. (13th June 2011) - Nada, Ahmed; Mohamed Ahmed, Ashraf; Vilallonga, Ramon; Armengol, Manuel; Moustafa, Ibrahim
Abstract : Diffusely enlarged thyroid glands (goitres) are becoming increasingly infrequent. However, in some geographical areas they are still relatively common and can cause compressive symptoms involving the trachea, oesophagus, and recurrent laryngeal nerve. Surgical treatment of diffusely enlarged thyroid glands requires a high level of expertise and may lead to severe complications. Here we present a case report of surgical treatment of an extremely enlarged thyroid gland, found in a 61-year-old female patient. The patient underwent surgery, and a thyroidectomy was performed. The resulting specimen weighed 4.7 kg (10.4 lbs). Histopathological examination revealed a multinodular goitre with multiple cysts and areas of haemorrhage and necrosis. Surgical excision can immediately resolve local symptoms and is often recommended when substernal extension is evident. To the best of our knowledge, this is the largest thyroid gland ever reported in the literature. Only experienced surgeons should treat large thyroid goitres. Ideally, large thyroid goitres should be treated before they reach a substernal component, otherwise any sudden growth in gland size could seriously compromise respiration.